Incorporating New Technologies in Teaching Paragraph Writing for Medical Doctors - Abdelouahab Boumaza (University of Eloued, 2019)
In this technology driven age, language teachers like in many other fields are more or less incorporating new technologies in their classrooms. A quick review of the wellknown methods of language teaching shows a fertile land to make good use of new technologies in developing and improving learners’ main skills. In a course designed to teach English for doctors, the classroom is rarely sufficient to achieve all the course objectives. This is partly due to the problem of time inconvenience usually associated with this kind of learners. Recourse to new technologies here could be a good remedy to overcome this limitation. Within a theme based approach new technologies’ tools and techniques are used to improve learner’s’ writing skills. This includes some in and out of class activities aiming to teach doctors how to write a paragraph in English
Keywords: paragraph writing; new technologies; Theme based approach; English for Doctors